Efektivitas Mindfulness Therapy dalam Meningkatkan Self Acceptance Remaja Broken Home: Literature Review - Amida Cindy Septiana; Abdul Muhid (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2022)
Divorce in parents will have an impact on the psychosocial condition of adolescents. The existence of parental divorce makes teenagers more vulnerable to having problems in the aspect of self-acceptance. Broken home teenagers often do some deviant behavior, such as skipping school, using illegal drugs, and so on. This is done by teenagers as an illustration that they have not been able to accept the conditions of the divorce. Thus, it is necessary to have psychological empowerment carried out for broken home teenagers to increase their self-acceptance. Purpose: The purpose of this literature review is to determine the effectiveness of mindfulness therapy in increasing self-acceptance of broken home adolescents. Method: The literature review method is used by collecting data about the phenomenon raised through various sources, both journals, books, and other references that are relevant to the issues and topics raised. Conclusion: mindfulness therapy is considered effective in increasing self-acceptance of broken home adolescents.